The Bilateral Engagement of India and Pakistan at Shanghai Cooperation Organization: Prospects and Challenges - Sarwat Rauf; Maira Tariq (NUST Journal of International Peace and Stability, 2023)
This article examines the complex relationship of Pakistan and India in the Shanghai Cooperation Organization (SCO). It points out cooperation pathways through steady advances in economic and security sectors. New Delhi and Islamabad have entered a puzzling state of affairs where both work for regional cooperation with serious bilateral frictions. In this context, the emphasis lies in highlighting the SCO as a favored platform for mitigating the rift between India and Pakistan, following thorough assessments of various alternatives. The argument is developed on the conjecture that establishing cooperation between rival states sometimes seems impossible, yet governments could enter into cooperative relations and collaborate through institutions. The central research question revolves around understanding how the SCO alleviates tensions between Pakistan and India.  It is discerned that the SCO’s gradual advances toward regional integration hold the potential to facilitate collaboration among member states. The study further examines various instances wherein India assumes responsible roles within the SCO, agreeing to take concerted actions for regional security and stability alongside other partners, including Pakistan.